A general synthetic route to 1-azabicyclo[m.n.0]alkenes via cyclisation based on α-sulfinyl carbanions - Manat Pohmakotr (2018)
A general synthetic route to 1-azabicyclo[m.n.0]alkenes via cyclisation based on α-sulfinyl carbanions was presented. The intramolecular nucleophillic addition of α-sulfinyl carbanions afforded 1-azabicyclo[m.n.0]alkenes in good yields. It is reported that the developed strategy should provide a general solution for the synthesis of various classes of 1-azabicyclic alkaloids.